Research on 5G MEC security assessment system and method - Qiucheng LU; Jinhui TANG; Congying BAO; Hao WU; Yusun FU (Dianxin kexue)
Multi-access edge computing (MEC) is deployed at the edge of the network, enabling efficient and fast data processing in mobile networks, while also undertaking important security functions, making MEC a prime target for attackers.Therefore, MEC nodes will face huge security risks.How to accurately evaluate and quantify MEC security capabilities is an urgent issue to be solved.For accurately evaluating and quantifying MEC security capabilities, the MEC safety assessment system was proposed in combination with MEC safety risks.The assessment indicators selected in the assessment system comprehensively reflect the basic characteristics of MEC and its complete safety capability.Based on this evaluation system, the MEC security evaluation method was designed by using the analytic hierarchy process (AHP) and fuzzy evaluation, the MEC vulnerability scoring system was creatively proposed, and the evaluation indicators were provided based on the results of MEC vulnerability scoring system, the MEC security capability quantification value was finally calculated.The experimental result proves the effectiveness of the method.